"We show that we are men": the Dominant Masculinity Profile of the Portoan Ultra-groups - Seabra Daniel (Sciendo, 2018)
The ultra-groups that support football clubs have been present in Portugal since the 1970s. Despite this support, performed with many chants and choreographies, the ultra-groups are reported mostly due to violent situations caused by their members. Based on an investigation of four ultra-groups that support football clubs in Oporto that was performed through lengthy observation, interviews, and surveys, this text highlights the characteristics of the dominant masculine profile present in these ultra-groups. The dimensions that allowed for the outline of this profile arise from theoretical perspectives reflecting gender and masculinity as an explanatory dimension of the aggressive behavior of hooligans and ultra-group members. These were briefly dealt in this text. They are composed of key features resulting from research about gender and masculinity in the Portoan ultra-groups, enabling their outlines. The physical and verbal violence, leadership profile, body display, homophobic discourse, and gendered exclusion expressed in the words, chants, and iconography of the ultra-groups allow for the definition of the key characteristics of the aggressive dominant masculine profile present in these Portoan ultra-groups.